1992
DOI: 10.1042/cs0830529
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of brain natriuretic peptide in acute hypoxaemic chronic obstructive pulmonary disease

Abstract: 1. Studies in vitro have recently shown that both atrial natriuretic peptide and brain natriuretic peptide have pulmonary vasorelaxant activity. The purpose of the present study was to evaluate for the first time whether plasma levels of brain natriuretic peptide are elevated in chronic obstructive pulmonary disease. Plasma levels of brain natriuretic peptide and atrial natriuretic peptide were therefore measured in 12 patients admitted with acute hypoxaemic chronic obstructive pulmonary disease [arterial part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 0 publications
2
42
0
2
Order By: Relevance
“…28,29) Furthermore, a study in patients with lone atrial fibrillation demonstrated a significant correlation between BNP levels and left atrial volume index, reflecting the production of BNP in a stretched left atrium. 30) A study by Inoue, et al, supported this hypothesis and suggested that the presence of atrial fibrillation should be taken into consideration when interpreting plasma BNP levels in patients with heart disease. 25) Moreover, Ohta, et al reported that atrial fibrillation raises plasma BNP levels, which is more marked if there is underlying structural heart disease present, and cardioversion reduces plasma BNP levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…28,29) Furthermore, a study in patients with lone atrial fibrillation demonstrated a significant correlation between BNP levels and left atrial volume index, reflecting the production of BNP in a stretched left atrium. 30) A study by Inoue, et al, supported this hypothesis and suggested that the presence of atrial fibrillation should be taken into consideration when interpreting plasma BNP levels in patients with heart disease. 25) Moreover, Ohta, et al reported that atrial fibrillation raises plasma BNP levels, which is more marked if there is underlying structural heart disease present, and cardioversion reduces plasma BNP levels.…”
Section: Discussionmentioning
confidence: 96%
“…The patient and control groups did not differ in terms of age (P = 0.722) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] mm) dimensions were significantly higher in patients with MS (all P < 0.001). No significant difference was detected between the groups regarding left ventricular end-diastolic diameter (P = 0.795), left ventricular end-systolic diameter (P = 0.110), and ejection fraction (P = 0.156).…”
Section: Preprocedural Clinical and Morphologic Variables And Plasma mentioning
confidence: 99%
“…BNP will change (generally rise) in response to valvular heart disease, 6 hypertensive heart disease, 7 pericardial disease 8 or pulmonary heart disease; 9 indeed, BNP is reliably not elevated in non-cardiac disease. 10 Hence, its highly attractive and wellchampioned sensitivity sits beside the relative frailty of diagnostic non-specificity, at least for a variety of cardiac conditions or cardiac responses.…”
Section: Bnp Does Not Simply Mark Ventricular Systolic Dimensions or mentioning
confidence: 99%
“…However, relatively little is known regarding the effects of angiotensin II on right heart and pulmonary blood flow in humans. The latter may be of relevance in that RAS activation with raised levels of angiotensin II occurs in patients with pulmonary hypertension due to cor pulmonale [4,5,6]. It is therefore interesting to consider whether elevated levels of angiotensin II might in part account for the altered haemodynamic status in cor pulmonale, in terms of producing raised right ventricular after-load and impaired left and right ventricular diastolic filling [7,8].…”
Section: Introductionmentioning
confidence: 99%